Shari'ah assessment on conflict of laws within the Islamic schools of jurisprudence. - Adam Sa'ad, Auwal; Abdul Haseeb, Ansari (Serial Publication Private Limited India, 2015)
Conflict of laws within the Islamic Schools of Law is one of the most complex concerns in Islamic law. However, the conflicts between the four Imams of the Schools have occurred mostly based on the genesis of Ijtihad done by them. It is understood that the main reason of conflicts was the natural differences between the Imams, coupled with the methodological differences which occurred mostly based on the ecological diversity and periodic differences. Imam Abu Hanifah for example was brought up in Kufah Iraq, at the time when the Prophetic traditions were not easy to get. Therefore, the use of reasoning was emphasized while solving fiqhi issues within the School. For the rest of the Imams they were at the time when the publication in Hadith had started and the fatawah based on personal reasoning were reduced, and this has really contributed to the conflicts within the Islamic Schools. The paper discusses this and concludes that the best way to resolve dispute is directly resorting to the Qur’an and Sunnah of the Prophet (s.a.w) (Prophetic traditions). More efforts should be given to the authenticated traditions reported from the authentic collections of ahadith such as Bukhary, Muslim and some others to march the evidences with the fiqh for easier understanding which might help in reducing the dispute amongst the contemporary followers of the four Islamic Schools of Law.